Mortality of Galleria mellonella L. by Beauveria bassiana (Balsamo) Vuill (Ascomycota: Hypocreales) - Hernández-Domínguez, Carmela; Zamora-Bernardino, Carmela; Vázquez-Cruz, Fabiel; Reyes-López, Delfino; Domínguez-Perales, Luís A.; Enríquez García, Fabián (Revista Mexicana de Ciencias Agrícolas, 2024)
One of the most commonly used fungi in pest control, which has a wide range of hosts, is Beauveria bassiana. This entomopathogen has adapted to different environments and can be found in several places, so in the present work, 60 soil samples were collected in 2020 in Acatlán de Pérez Figueroa, Oaxaca, by means of Galleria mellonella, used as bait for its isolation. Five isolates were obtained from this procedure, which were evaluated in larvae of Galleria mellonella at 24, 48, 72, 96, 120, 144, and 168 h in order to know their efficacy in mortality and mycosis. In the methodology, the DNA of the fungi was extracted and the ITS region of the 5.8S rRNA gene was amplified by PCR, the product was sequenced and the sequences were compared with others existing at the National Center for Biotechnological Information. The result was one isolate of Beauveria pseudobassiana and four of Beauveria bassiana, of which isolate 11 showed 100% mortality and mycosis at 96 h, unlike the commercial isolate and the control, which needed an additional 72 h to kill all larvae, in addition to showing 20% and 60% of mycosis, respectively. The time of 96 h was significantly different (p≤ 0.05) because during this time, most of the larvae died and mycosis occurred. Identifying entomopathogenic fungi and conducting studies of their effectiveness in larvae facilitates the start of new research experiments.
Keywords: Beauveria bassiana; Galleria mellonella L.; DNA; efficacy; isolate; time